Assessing Structural Racism Measures on Health Outcomes of Asian Americans, Native Hawaiians, and Pacific Islanders: A Scoping Review - Raman, Priya; Chu, Christina T.; Chong, Stella K.; Mukherjea, Arnab; Kue, Jennifer (Journal of racial and ethnic health disparities, 2025)
Background Limited literature exists on structural racism measures on health outcomes for Asian Americans, Native Hawaiians, and Pacific Islanders (AAs and NH/PIs). AAs and NH/PIs make up approximately 6.2% of the U.S. population and consist of diverse ethnic subgroups with distinct languages, cultures, religions, socioeconomic statuses, and historical backgrounds. The lack of disaggregated data collection and contextualized measures hinders our understanding of how structural racism affects health outcomes in these populations. Methods We conducted a scoping review to assess the extent to which measures of structural racism are used in research with AAs and NH/PIs. Databases, including CINAHL, EBSCO, PsychINFO, PubMed, Scopus, and Social Science Citation Index, were searched for peer-reviewed articles on the measures of and empirical impacts of structural racism on AA and NH/PI health. We identified 23 full-text articles from a pool of 11,660 screened articles. Four articles were included in the final analysis. Results Among the selected studies, two studies identified an association between racial segregation and mental and behavioral health outcomes within AAs and NH/PIs. The other two studies found redlining on chronic health outcomes in these communities. These studies uncovered associations between government systems and policies and AA and NH/PI health outcomes. Discussion Existing measures may not adequately capture the complex relationships between structural racism and health outcomes in AAs and NH/PIs. Future research should contextualize and operationalize the multifaceted manifestations of structural racism unique to AAs and NH/PIs to achieve health equity.